ANALISIS KINERJA SIMPANG EMPAT BERSINYAL DENGAN METODE MKJI 1997 : STUDY KASUS PERSIMPANGAN JALAN GENTENG KALI – JALAN GEMBLONGAN – JALAN PRABAN – JALAN TUNJUNGAN - Muhammad Fathul Bary; Hary Moetriono (LPPM Universitas Bina Bangsa, 2023)
The occurrence of congestion is due to the buildup of vehicle volume at certain hours so that the accumulation of vehicles causes a halt in the flow of traffic at a highway intersection. The existence of shops and schools around the road section greatly influences the increase in vehicle volume, especially the side obstacle factor which is quite large, such as pedestrians and parking vehicles, especially 4 wheeled vehicles. The method used in this study is the Indonesian Highway Capacity Manual Year 1997 (MKJI 1997). Researchers conducted a traffic survey of the number of vehicles passing for 3 days, namely Tuesday, Wednesday, and Thursday, it can be calculated the amount of traffic volume, intersection capacity, and the degree of saturation. From the results of the study, the highest traffic volume at the intersection of Praban Street, Gemblongan Street, Genteng Kali Street, Surabaya City occurred on Tuesday at 17.00-18.00 WIB. Jalan Praban (West) amounted to 1.712 smp/hour, Jalan Gemblongan (North) amounted to 3.216 smp/hour and Jalan Genteng Kali (East) amounted to 1.431 smp/hour. The results of the existing performance at the intersection of Praban Street, Gemblongan Street, Genteng Kali, Surabaya City with intersection type 333 occurred on Tuesday at 17.00-18.00 WIB, having an average saturation level of 0,81